Experimental study of tunnel sidewall effect on flame characteristics and air entrainment factor of methanol pool fires. (5th June 2016) - Gao, Z.H.; Liu, Z.X.; Ji, J.; Fan, C.G.; Li, L.J.; Sun, J.H.
Highlights: A set of burning experiments were conducted in a reduced scale tunnel model. The flame characteristics are analyzed by dimensionless analysis. Correlations for the confined flame height are proposed and compared to previous results. The air entrainment factor for the confined plume is quantified and analyzed. Abstract: This paper presents an experimental investigation to explore the effect of tunnel sidewall on flame characteristics and air entrainment factor of methanol pool fires with decreasing distance to the sidewall. Experimental results show that owing to the confinement effect of sidewall, the flame height increases with the decrease of fire-sidewall distance. Especially for fire immediately against sidewall, the air entrainment process is confined to the largest extent and the flame height increases significantly. Correlations of the flame height with difference distances to the sidewall are obtained based on the dimensionless analysis and experimental data. Besides, the Entrainment Factor (EF), which describes the ratio of air entrainment into the confined plume relative to the unconfined one, is estimated for different fire locations. When fire is flush with sidewall, the Entrainment Factor (EF) decreases to 0.46, meaning that only 0.46 times of air is entrained into the flame volume compared to the fire at the longitudinal centerline of tunnel. The flame height and Entrainment Factor under the experimental conditions are also compared to the previous results.